Brief records of service for Christ in many lands -- 1896-1947 - Harvey, James G. (Palmerston North, NZ Gospel Publishing House, 1947)
Includes index and photos.
Brethren writer.
Keywords: Missionaries from New Zealand -- Brethren Movement